Progressive high-fluence epithelium-on accelerated corneal crosslinking: a novel corneal photodynamic therapy for early progressive keratoconus - Mazzotta, Cosimo; Pandolfi, Anna; Ferrise, Marco (Frontiers in Medicine, 2023)
Purpose To assess the preliminary clinical results of a new, progressively higher fluence-pulsed light Epi-On accelerated crosslinking nomogram (PFPL M Epi-On ACXL) in the treatment of progressive keratoconus (KC). Setting Siena Crosslinking Center, Siena, Italy. Methods A prospective pilot open, non-randomized interventional study, including 32 eyes of 32 young-adult patients over 26 years old with Stages I-III progressive KC undergoing PFPL M Epi-On ACXL, was conducted. Riboflavin loading was performed by using Paracel I 0.25% for 4 min and Paracel II 0.22% for 6 min. The Avedro KXL System (Glaukos-Avedro, Burlington, USA) was used for pulsed-light accelerated crosslinking (ACXL) at air room 21% oxygenation and 13 min of UV-A irradiation. The treatment fluence was set at 7.2 J/cm2, 8.6 J/cm2, and 10.0 J/cm2 in corneas with baseline pachymetry <420 μm (group 1: 8 eyes), ≥ 420 μm <460 μm (group 2, 11 eyes), and ≥ 460 μm (group 3, 13 eyes), respectively. Uncorrected distance visual acuity (UDVA), best-spectacle corrected visual acuity (BSCVA), Scheimpflug corneal tomography, and anterior segment OCT (AS-OCT) data were collected at baseline and postoperatively at 1, 3, and 6 months. Results UDVA and BSCVA improved in all groups (P ≤ 0.05). Maximum keratometry values (K max) showed a significant decrease in the 10.0 J/cm2 group (Δ −1.68 D). The coma (HOAs) value improved significantly by the sixth month in all groups. OCT average demarcation lines were 211 ± 19 μm in group 1, 245 ± 23 μm in group 2, and 267 ± 21 μm in group 3. Conclusions The preliminary results show that pachymetry-based PFPL M Epi-On ACXL nomogram stabilizes ectasia progression. Higher fluence Epi-On ACXL increases CXL penetration, with better functional outcomes in the absence of complications.